Tyrosinase inhibitor screening in traditional Chinese medicines by electrophoretically mediated microanalysis. Issue 16 (14th July 2015) - Tang, Lilin; Zhang, Wenpeng; Zhao, Haiyan; Chen, Zilin
<x xml:space="preserve">Abstract</x> A capillary‐electrophoresis‐based method for the screening of tyrosinase inhibitors in traditional Chinese medicines was developed. The method integrated electrophoretically mediated microanalysis with sandwich mode injection, partial filling, and rapid polarity switching techniques, and carried out on‐column enzyme reaction and the separation of substrate and product. The conditions were optimized including the background electrolyte, mixing voltage, and the incubation time. Finally, the screening of nine standard natural compounds of traditional Chinese medicines was carried out. The inhibitors can be directly identified from the reduced peak area of the product compared to that obtained without any inhibitor. Chlorogenic acid (100 μM) showed inhibitory activity with the inhibitory percentage of 19.8%, while the other compounds showed no inhibitory activity. This method has great application potential in drug discovery from traditional Chinese medicines.